Anxiety is not the right choice! Individual differences in trait anxiety modulate biases in pseudoneglect - Righi, Stefania; Benedetti, Viola; Giganti, Fiorenza; Turano, Maria Teresa; Raduazzo, Greta; Viggiano, Maria Pia (Frontiers in Human Neuroscience, 2023)
Pseudoneglect, the tendency to display a leftward perceptual bias, is consistently observed in line bisection tasks. Some studies have shown that pseudoneglect is sensitive to emotions. This emotionrelated modulation is likely related to the valence-dependent hemispheric lateralization, although the results do not converge. A possible explanation for these inconsistencies could be individual differences in emotional tone. Considering that negative and positive emotions produce a different basic activation of the two hemispheres, emotional characteristics of the subjects, such as trait anxiety, could in fact modulate the pseudoneglect phenomena. To verify this, high-and low-anxiety participants were asked to centrally bisect horizontal lines delimited by neutral or emotional (happy and sad) faces. In line with previous studies, results here showed a decrease of the leftward bisection error in the presence of happy faces indicating a greater involvement of the left hemisphere in processing emotional positive stimuli. In addition, trait anxiety influenced the magnitude of visual bias. High-anxiety subjects, compared to low-anxiety subjects, showed a general bias in visual attention toward the left space as function of emotional valence. Results are discussed within the framework of the valence-dependent hemispheric specialization and relative degree of activation. In sum, our data highlight the relevance of considering emotional individual differences in studying the pseudoneglect phenomena.